Partycypacja społeczna dzieci. Szkic dynamiki dyskursu - Jarosz, Ewa (Chowanna, 2019)
In the contemporary world social participation of children is seen as an idea that should be implemented at various social levels. The idea itself is understood multi-dimensionally – as various social activities, including the participation in decision-making processregarding children’s matters. Today in a discourse on children’s participation its collective dimension is accented, which means social participation and access to social and civil goods of children as a social group. In the discourse on participation, which has been developing dynamically since the adoption of the Convention on the Rights of the Child, various theories are used as a background against which children’s participationis considered and justified. The paper presents an outline of this problem and current tendencies in the discourse.